2023
DOI: 10.1093/ckj/sfad139
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid receptor antagonist use in chronic kidney disease with type 2 diabetes: a clinical practice document by the European Renal Best Practice (ERBP) board of the European Renal Association (ERA)

Abstract: Chronic kidney disease (CKD) in individuals with type 2 diabetes (T2D) represents a major public health issue; it develops in about 30-40% of patients with diabetes mellitus and is the commonest cause of CKD worldwide. Patients with CKD and T2D are at high risk of both developing kidney failure and of cardiovascular events. Renin-angiotensin system (RAS) blockers were considered the cornerstone of treatment of albuminuric CKD in T2D for more than 20 years. However, the residual risk of progression to more adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 143 publications
0
4
0
2
Order By: Relevance
“…Über den Mineralokortikoid-Rezeptor werden Entzündungs-und Fibroseprozesse an Herzen und Nieren unterhalten, was zu einer CKD-Progression durch Albuminurie und Glomerulosklerose führt [27]. Auch steroidale MRA hatten bereits zuvor einen albuminuriesenkenden Effekt gezeigt, weswegen ein progressionsverlangsamender Effekt nahelag [28]. Dies konnte später ebenso für Finerenon belegt werden [26].…”
Section: Finerenonunclassified
“…Über den Mineralokortikoid-Rezeptor werden Entzündungs-und Fibroseprozesse an Herzen und Nieren unterhalten, was zu einer CKD-Progression durch Albuminurie und Glomerulosklerose führt [27]. Auch steroidale MRA hatten bereits zuvor einen albuminuriesenkenden Effekt gezeigt, weswegen ein progressionsverlangsamender Effekt nahelag [28]. Dies konnte später ebenso für Finerenon belegt werden [26].…”
Section: Finerenonunclassified
“…Three randomized studies evaluated the effect of esaxerenone on albuminuria in patients with CKD and type 2 diabetes. A dose-dependent reduction in albuminuria was present in all three studies, and clinically significant hyperkalemia was rarely reported (4–9% of patients) [ 61 ]. A meta-analysis by Jiang et al (2022) showed that the use of nonsteroidal MRAs (finerenone, apararenone, and esaxerenone) in patients with type 2 diabetes and CKD reduced albuminuria and systolic blood pressure without an excess risk of serious adverse events.…”
Section: The Switch From Steroidal To Nonsteroidal Mineralocorticoid ...mentioning
confidence: 99%
“…1). Основным принципом нефропротекции у пациентов с СД2 и ХБП в настоящее время является совокупное назначение трех классов «болезнь-модифицирующих» препаратов (иАПФ/БРА, иНГЛТ-2, финеренон) [35][36][37][38][39][40][41].…”
Section: место финеренона в клинических рекомендацияхunclassified